Enhancement of lac dye adsorption on cotton fibres by poly(ethyleneimine) - Janhom S. (2014)
The effect of poly(ethyleneimine) (PEI) on the adsorption and desorption of lac dye (Natural dye 25; CI 75450) on cotton fibres is reported. We show that PEI increases the dye adsorption and decreases any subsequent desorption of lac dye from the cotton fibres. At equilibrium, the ratio of the number of molecules of lac dye per ethyleneimine repeat unit is ∼1 in solution but it is close to 3.5 when the PEI adsorbed to the cotton. This suggests that the building is electrostatic in character. The effect of NaCl on the adsorption and desorption of lac dye on cotton fibres has therefore been investigated. It is found that the amount of lac dye adsorbed on fibres increases when NaCl is present in the lac dye solution, but the amount that may be desorbed also increases. © 2004 Elsevier Ltd. All rights reserved.